SOUND POLLUTION IN THE FURNITURE INDUSTRY OF THE FEDERAL DISTRICT - Lima, Clarissa Melo; da Costa, Tito Ricardo Vaz; de Almeida, Alexandre Nascimento; Gonçalez, Joaquim Carlos (Seven Editora, 2026)
The paper presents an evaluation of sustainable practices in furniture industries through the analysis of their productive processes. Sound pollution was studied in two furniture wood industries of different sizes of the Federal District. Through measurements it was possible to measure the excessive noise emissions and compare them with the standards established by existing national and international Laws, Resolutions, Ordinances and Regulatory Technical Standards. Excess noise was observed in both industries at specific points. To control the problem, actions were suggested based on the good practices of sustainable projects. DOI: https://doi.org/10.56238/sevened2026.008-037